Improving Students' Speaking Ability by Creating a Story Telling Recorded in a Video - Futuh Handoyo; Lia Agustina; R. Setiwan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Technology helps a lot on the education field. By implementing technology, it would influence on the atmosphere either on students' motivation or on language itself. Oral communication is an essential skill which could help students' life in the future. The most students’ problem in studying English is expressing ideas. Some experts said that storytelling can be used to improve students' learning to express oral communication. Connecting with this idea, the researches decided the purpose of the study by improving the students’ speaking ability with producing a storytelling created in the form of a video component. The researchers used an Action Research, The students were required to create a cartoon story, voiceover narration, and background music that produced in a video presentation. The object of the research was 30 students of the Accounting Department of 2 nd Semester 2023. The result of the study was significantly improved which could be seen from the mean of the first project which amounted as big as 77,33, while on the second project, the amount was 83,16. The evaluation kept increased in every evaluation. The conclusion stated that the model was successfully implemented. Key words: Improving, Speaking Ability, Storytelling, Video